Japanese economic growth : trend acceleration in the twentieth century - Ohkawa, Kazushi; Rosovsky, Henry (Stanford, Calif. : Stanford University Press, 1973)
This book provides an highlights about international cooperation and Japan economic growth.
Includes bibliographical references.
oo 08/08/2018
Loans
Keywords: Economic history; Economic policy; Economic growth; Japan